Tindak Pidana Pembunuhan Yang Dilakukan Oleh Remaja Terhadap Balita - Fuadi Isnawan (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, Indonesia, 2020)
Adolescence is a period where adolescents look for their identity. The search for his identity will also be influenced by several internal and external factors. This factor will affect the identity of adolescents. Adolescents who get factors that are less supportive in the search for their identity will have a distorted identity and tend to be more wicked in character or who are more subtle. This deviation does not bring the teenager to do some acts that are prohibited by law, can be mild or severe actions. One of the things that made me astonished was the teenagers who carried out sadistic killings and tended to be calm in executing their victims. How can a young teenager have thoughts of killing and he feels satisfied with it. This raises the question, why can such intentions arise? In this article, we will discuss why this can happen, which will be dialysisist in Criminology combined with Legal Psychology. These two analysis blades will help to answer why this happened. From this article we can take it as a joint learning so that we evaluate ourselves and society so that we do not encourage someone to do evil, either consciously or unconsciously. Keywords: Murder, Social Control Theory, Adolescents